Application of Electronic-Student Worksheets Based on a Scientific Approach to Train Students' Critical Thinking Skills of Bryophytes Material - Ariska, Della Ayu; Indah, Novita Kartika (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
Critical thinking is an essential skill that students must have in the 21st century. The scientific approach is able to train students to think critically. This research aims to describe the implementation of E-LKPD based on a scientific approach, implementation of learning, students' critical thinking skills, and students' responses. This research is referred to as quasi-experimental research. In this research, a